Dialogic Feminist Gathering and the Prevention of Gender Violence in Girls With Intellectual Disabilities - de Mello, Roseli Rodrigues; Soler-Gallart, Marta; Braga, Fabiana Marini; Natividad-Sancho, Laura (Frontiers in Psychology, 2021)
Adolescent gender-based violence prevention and sexuality education is a topic of current concern given the increasing numbers of violence directed at girls. It is known that almost one in three girls aged 15-19 years has experienced gender-based violence in their sexual relationships (WHO, 2018). According to a World Bank report (2019), this risk could reach three to four times higher for girls with disabilities. Following the good results obtained in the research project "Free_Teen_Desire" led by the University of Cambridge and funded by the Marie Curie Actions Program in the prevention of gender violence in adolescents through Dialogic Feminist Gatherings (DFG), the aim of the study is to analyze its transfer and impact on adolescent girls with intellectual disabilities. The Dialogic Feminist Gatherings are here understood as generators of a more dialogic environment for girls in general and we wonder if and how it is extended to the context of girls with disabilities. Thus, the research takes the form of a case study with a communicative approach on a Dialogic Feminist Gatherings (DFG). The intervention is carried out in a special school located in Valencia during the 2018-2019 and 2019-2020 academic years with a group of 19 non-mixed female students, female teachers, and the mother of one of the students. The study analyzes which are the transfer criteria to incorporate the DFGs in a special education context and what is their impact on the prevention of gender violence in girls with disabilities. The data collection techniques consist of two in-depth interviews, analysis of the field diary of twenty-four intervention sessions, and a focus group with seven teachers. It is demonstrated that Dialogic Feminist Gatherings are successfully transferred to the special education context of the case study. The results show how contexts of safety, solidarity, and friendship are generated which protect adolescent girls with disabilities from relationships with gender violence.